1989
DOI: 10.1128/jvi.63.11.4850-4856.1989
|View full text |Cite
|
Sign up to set email alerts
|

The reovirus M1 gene, encoding a viral core protein, is associated with the myocarditic phenotype of a reovirus variant

Abstract: Reoviruses contain a genome composed of 10 double-stranded RNA gene segments. A reovirus reassortant, 8B, derived from type 1 Lang (TlL) and type 3 Dearing (T3D), displayed a phenotype unlike that of either of its parents in that it efficiently induced numerous macroscopic external cardiac lesions in neonatal mice (B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…Association of antagonism of IFN signaling with induction of myocarditis. Previous studies using a panel of reovirus reassortants identified the reovirus M1 gene as a determinant of reovirus strain-specific differences in induction of myocarditis in mice (60). In addition, reovirus strain-specific differences in induction of and sensitivity to IFN-␣/␤ are associated with protection against myocarditis.…”
Section: T1l Represses Ifn Induction Of a Subset Of Isgsmentioning
confidence: 99%
“…Association of antagonism of IFN signaling with induction of myocarditis. Previous studies using a panel of reovirus reassortants identified the reovirus M1 gene as a determinant of reovirus strain-specific differences in induction of myocarditis in mice (60). In addition, reovirus strain-specific differences in induction of and sensitivity to IFN-␣/␤ are associated with protection against myocarditis.…”
Section: T1l Represses Ifn Induction Of a Subset Of Isgsmentioning
confidence: 99%
“…Reoviruses, in contrast, are not associated with serious human disease, but provide an excellent model for study of viral pathogenesis in neonatal mice (Schiff and others 2007). Studies using reovirus reassortants have identifi ed the viral determinants of tropism and disease in the central nervous system (Weiner and others 1977) and heart (Sherry and Fields 1989;Sherry and Blum 1994), and replication in the gastrointestinal tract for spread to other animals (Keroack and Fields 1986;Bodkin and Fields 1989). The structure of the whole virion has been resolved by cryoelectron microscopy (Dryden and others 1993), and the reovirus core has been solved to 3.6 Å resolution (Reinisch and others 2000).…”
mentioning
confidence: 99%
“…In addition to determining differences in viral yield in cultured cells, the L1 and M1 genes also play important roles in some models of reovirus pathogenesis. The L1 and M1 genes are linked to differences in the capacities of reovirus strains to produce myocarditis in immunocompetent mice (35,36), and, along with the L2 and S1 genes, L1 and M1 are associated with strain-specific differences in reovirus virulence in severe combined immunodeficiency mice (13). It is not known how viral gene products involved in RNA synthesis influence viral growth and virulence; however, it has been suggested that they alter the kinetics of viral polymerase activity in particular host tissues or exert toxic effects on the cell (1,13,36).…”
mentioning
confidence: 99%
“…The reassortants do not segregate into discrete groups based on genotype; rather, they form a continuum with ranges exceeding those of either parent. Nonetheless, the use of a large reassortant panel and sensitive statistical techniques allowed us to identify the primary genetic determinants of the observed phenotypic differences, as has been done in several previous studies (13,22,23,35,36,40,41). Based on the R 2 values obtained by linear regression, we estimate that the viral S1 and M2 genes together account for 54% of the genetically determined variance in reovirus-induced apoptosis of MDCK cells and that the viral L1 and M1 genes together account for 52% of the genetically determined variance in reovirus growth in MDCK cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation